Hygiene in the home - Stokes, Ruth (My University, 1892)
Introduction: To be healthy, wealthy and wise is the ambition of all people without exception. Of these three to be healthy is the most importance. Health should be prized above everything else. Without health no man can be happy. No man can make the half of himself that he would otherwise have made if he has a shattered brain and a weak body. Health is one of the few things that money cannot purchase and yet there is nothing about which people are so careless and neglectful. People seem to think that their bodies are their own and that they have the right to abuse them in the way that pleases them best. Is it true that our life is our own? It is our own only so far as it is our duty to preserve and make the best of it that lies within our power. People who would look with horror upon one who would think of committing suicide, violate the laws of health constantly and by so doing shorten their lives and endure much suffering while they live. There are certain sanitary laws layed down in the Bible which were strictly adhered to by the Jewish people. There is not a people recorded in history who were as free from hereditary and contagious diseases as were the Jews. In those days one was reproached if he had ill health and the preservation of the health was considered to be a religious duty which under no circumstances must be neglected or overlooked.
Citation: Stokes, Ruth. Hygiene in the home. Senior thesis, Kansas State Agricultural College, 1892.
Morse Department of Special Collections
Keywords: Hygiene; Cleanliness; Home; Religion; Home economics; Theses; Manuscripts (documents)